Membaca Kritis dapat Meningkatkan Kemampuan dalam Pengambilan Keputusan - Dwi Norma Apriyanti; Lathifah Sekar Fitriarini; Meyliana Putri; Mahmudah Fitriyah Z.A. (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The purpose of this study is to examine how much critical reading skills affect individuals in their life. Critical reading becomes an essential skill to distinguish between reliable information and not, as well as to understand the implications and consequences of a decision. By reading critically, one can identify different perspectives, consider relevant facts, and develop a deeper understanding of an issue before making a decision. The method of writing this article uses library research, a method of collecting data by understanding and studying the theories of various literature related to research. Decision-making ability cannot arise naturally, but needs to be built and trained in children early. One effective method for improving decision-making ability is to train critical reading skills. Critical reading is a process of analysis of the content of the text, in which the reader uses the critical thinking process to evaluate and decide whether to accept or reject information submitted by the author.